A influência do catolicismo na educação de Porteirinha/MG (1937-1962) - Silva, Wilney Fernando (2018)
This research is linked to the History and Historiography of Education research line of the Graduate Program in Education and has as general objective to investigate the influence of the Catholic Church in education in Porteirinha/MG, from 1937 to 1962. Without losing sight of as the conception of the Perfect Society Church came and was disseminated in the north of Minas Gerais and Porteirinha, we will analyze the influence of the Church with the press, the family and politics, important spaces in which informal education takes place. In order to understand the influence of the Church in formal education, we chose the João Alcantara School Group, the main educational institution of Porteirinha, as the locus of the study. The temporal clipping includes the period between 1937, when this School Group was installed, in 1962, when the Second Vatican Council and, consequently, the break with the Perfect Society conception. The cut also coincides with the period of greater performance of Father Julião Arroyo Gallo, central figure in the research, ahead of the Parish São Joaquim de Porteirinha. The thesis defended in the work is that the Romanization movement in the north of Minas Gerais, during the studied period, promoted the dissemination of the concept of Church Perfect Society. This Tridentine vision stimulated, through various strategies, the expansion of the influence of the Catholic Church in education in Porteirinha. Thus, in addition to influencing the public space of formal education, Catholicism has achieved dominion over the family, the press, and local power groups. As a research method, we propose bibliographical research, carried out in books, articles in scientific journals, dissertations and theses; and documentary research, which includes the consultation and analysis of several local and regional newspapers, books of minutes of the teachers meetings, school bulletins, fall books of some parishes in the north of Minas Gerais, photo albums, minutes of the meetings of the religious associations of the city of Porteirinha, official documents of the State, such as the books of laws and decrees of the Municipality of Porteirinha, as well as constitutions, laws and decrees of Minas Gerais and the Federal Government; the documents of the Catholic Church as encyclicals and pastoral letters close the documentary corpus of the research. As a conclusion, we find that the dissemination of the concept of the Perfect Society Church in Porteirinha through the Romanization movement took place more effectively after the creation of the São Joaquim Parish in 1941 and the arrival of Father Julião, who contributed to the development of the material and spiritual aspects of the new parish. In order to maintain its influence in the political field, the Church sealed important covenants with those in power, brought together people from society in their religious associations, and used the press to influence behavior and conduct through the circulation of newspapers, serials, books, etc. which spread Catholic doctrine and moralizing customs. These actions strengthened the Church's power over family, schooling, and bodily practice. The School Group valued and idealized the moralizing dimension of teaching and the emphasis on Catholicism in society. We concluded that the formation of the children had as its guiding principle the teachings of the Catholic Church, and even within the public space, it was indispensable that the teaching and organization of the school, as faculty and students, programs, planning, calendar and projects, be governed by conservatism, under the watchfulness and blessings of the Catholic Church.